Homicide by Gagging: A Case Report - Zanjad, N P; Dake, M D; Bhosle, S H; Godbole , H V (Journal of Indian Academy of Forensic Medicine, 2014)
Gagging is a form of asphyxia which results from forcing a gag such as rolled up cloth, paper etc. deep in to the mouth or oropharynx. As such asphyxia by gagging is rare in occurrence and usually seen in infants and children as homicidal act or in adults suffering from psychiatric disorder as suicidal form of gagging. As young ones and elder people are easily overpowered due to least resistance offered by them, the homicidal gagging is more common in this age group. We report a case of gagging in unknown newborn male which was found in polythene bag in open garbage area. During autopsy a rolled up cloth was observed in buccal cavity and on internal examination the gag was seen deep inside the mouth surrounded by mucus. In such cases, meticulous examination of nasopharynx, oropharynx and gag material is important.